Non‐tuberculous Mycobacteria isolated from lymph nodes and faecal samples of healthy slaughtered cattle and the abattoir environment. Issue 3 (17th December 2017) - Ghielmetti, G.; Friedel, U.; Scherrer, S.; Sarno, E.; Landolt, P.; Dietz, O.; Hilbe, M.; Zweifel, C.; Stephan, R.
Summary: Infections caused by non‐tuberculous mycobacteria (NTM) are reported as emerging disease in many countries worldwide. The occurrence of NTM in different hosts and their implication as obligate or opportunistic pathogen remain largely unclear. Lymph nodes and faecal samples of clinically healthy Swiss cattle at slaughter were analysed for the presence of NTM. Based on the examined lymph nodes, NTM were detected in 20% of 108 cattle originating from different premises. The 22 isolates belonged to five different species of Mycobacteria ( M. avium subsp. hominissuis, M. kansasii, M. persicum, " M. lymphaticum" and M. europaeum ). M. avium subsp. hominissuis (63%) and M. kansasii (18%) thereby predominated and were found in lymph nodes with and without macroscopic changes. Moreover, M. persicum found in two cattle has recently been described as a human pathogen and is closely related to M. kansasii . Amongst cattle with lymph nodes positive for mycobacteria, viable NTM were occasionally also detected in bovine faeces. However, the isolated NTM species from lymph nodes and respective faecal samples ( M. hassiacum, M. phlei and M. vaccae ) did not coincide. Moreover, NTM species identified amongst isolates from the slaughterhouse environment clearly differed from those from lymph nodes and faecal samples, excluding cross‐contamination of the tissue specimens through the environment or laboratory processing. Assuming that some NTM interfere with the detection of bovine tuberculosis (bTB), the present findings in healthy animals emphasize the need of more specific diagnostic tools for bTB eradication programs.